The African Christian diaspora: new currents and emerging trends in world Christianity - Adogame, Afe (Bloomsbury Academic, 2013)
Trajectories of African migration -- Narratives of African migration -- Situating the local scene(s) -- Historiography of new African Christianities in diaspora -- A phenomenology of African Christian communities in diaspora -- African Christianities as social, cultural and spiritual capital -- Negotiation identity, citizenship and power -- Globalization, media and transnationalism -- Reverse mission -- The politics of networking.